The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/1472-6963-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Guideline adherence and patient satisfaction in the treatment of inflammatory bowel disorders – an evaluation study

Abstract: BackgroundCrohn's disease (CD) and ulcerative colitis (UC) are the most frequent inflammatory bowel disorders (IBD). IBD cause a significant burden to society due to extensive health care utilization from the first clinical symptoms until diagnosis and thereafter due to direct and indirect costs. Besides the socio-economic impact of CD and UC, gastrointestinal and extraintestinal symptoms affect quality of life, but there is remarkably little data about the quality of treatment as assessed by patient satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
0
16
0
3
Order By: Relevance
“…In IBD prodromes of between 4 and 4.5 years have been reported: n = 66, median 7.7 years ± 10.7 years in Crohn's disease; median 1.2 ± 1.8 years in ulcerative colitis [3]; n = 86 of which 19% had a mean prodrome of 4 years or greater [4]. Furthermore, prodromes of 11-year duration were recently reported in The Manitoba IBD Cohort Study (n = 112, mean duration 11 years, ranging from 3 to 48 years) [5].…”
Section: Introductionmentioning
confidence: 97%
“…In IBD prodromes of between 4 and 4.5 years have been reported: n = 66, median 7.7 years ± 10.7 years in Crohn's disease; median 1.2 ± 1.8 years in ulcerative colitis [3]; n = 86 of which 19% had a mean prodrome of 4 years or greater [4]. Furthermore, prodromes of 11-year duration were recently reported in The Manitoba IBD Cohort Study (n = 112, mean duration 11 years, ranging from 3 to 48 years) [5].…”
Section: Introductionmentioning
confidence: 97%
“…The few studies having looked at adherence to guidelines among gastroenterologists have revealed equivocal results 30,31 . However, the treatment of CD appeared to be appropriate in most patients according to cohort studies from Switzerland and Europe 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies assessed patients’ perceptions on benefits and risks of anti-TNF treatments,31,32 but to our knowledge, satisfaction with treatment has been poorly reported in the literature 10. The SPACE © questionnaire is thus the first tool to assess patient satisfaction with anti-TNFα treatment in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Quality-of-life studies were performed in inflammatory bowel diseases,8,1417 in clinical trials, HRQL was used as a secondary endpoint 12. However, no study has assessed patients’ satisfaction in CD 10. A recent prospective study showed that despite the preference of CD patients for adalimumab versus infliximab for maintenance, a proportion of patients returned to infliximab due to intolerance, supporting the importance of patients’ outcomes in patients’ behavior towards CD’s therapeutics and their efficacy 18…”
Section: Introductionmentioning
confidence: 99%